2020
DOI: 10.1111/sed.12751
|View full text |Cite
|
Sign up to set email alerts
|

The influence of basin setting and turbidity current properties on the dimensions of submarine lobe elements

Abstract: Submarine lobes have been identified within various deep-water settings, including the basin-floor, the base of slope and the continental slope. Their dimensions and geometries are postulated to be controlled by the topographic configuration of the seabed, sediment supply system and slope gradient. Ten experiments were conducted in a three-dimensional-flume to study the depositional characteristics of submarine lobes associated with: (i) different basin floor gradients (0 to 4°); (ii) different sediment concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 95 publications
(217 reference statements)
4
30
0
Order By: Relevance
“…The deposit widened from 80 cm at the base‐of‐slope, to 200 cm at a distance of 280 cm from the slope break. Between distances of 80 and 160 cm from the slope break there is a 50 cm wide anomalously thin zone ( ca 1 cm thinner than the surrounding deposits), similar to convex indents described by Spychala et al (2020), interpreted to represent a bypass‐dominated area in a channel to BFD transition zone (Figures 3 and 5). At the centroid, the axis of the deposit was >5 cm thick for a width of ca 80 cm.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The deposit widened from 80 cm at the base‐of‐slope, to 200 cm at a distance of 280 cm from the slope break. Between distances of 80 and 160 cm from the slope break there is a 50 cm wide anomalously thin zone ( ca 1 cm thinner than the surrounding deposits), similar to convex indents described by Spychala et al (2020), interpreted to represent a bypass‐dominated area in a channel to BFD transition zone (Figures 3 and 5). At the centroid, the axis of the deposit was >5 cm thick for a width of ca 80 cm.…”
Section: Resultssupporting
confidence: 73%
“…Alexander et al (2008) showed that slope gradient was a primary control on the development of a lateral ridge with flows able to maintain forward momentum upon exiting the channel. Similarly, Pohl et al (2020a) document that the slope gradient is a stronger control on sediment bypass and depositional patterns at break‐of‐slope compared to basin floor gradient (see also: Spychala et al, 2020). Therefore, systems with steeper channel gradients, at least immediately up‐dip of lobes, may be more probable to develop finger‐like geometries due to focused axial flow components.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…14). These results suggest that submarine lobes may be much larger than previously estimated, as also suggested by recent flume tank experiments (Spychala et al 2020). This opens the possibility of identifying (and predicting) the presence or absence of genetically linked deep-water basin-floor sandstone accumulations by the careful examination of deep-water mudstones along basin margin successions.…”
Section: Implications For Dimensions and Geometries Of Lobessupporting
confidence: 79%